Detection of limestone deposits in the Nyanda mountain range, Masvingo, using ground magnetic geophysical survey. - Chipokore, Simbarashe (Midlands State University, 2017)
Geophysical survey techniques have successfully been applied to near-surface limestone detection in karstic terrains. A magnetic geophysical survey to delineate the karstic structure of the Nyanda Mountains, Masvingo, was carried out in the interest of mapping out limestone deposits required for cement production. The magnetic-total-field-anomaly maps helped reveal the metamorphic and sedimentary units in the study area. Although only part of the mountain range was surveyed for this project, the results suggested that the buried limestone units had an undulating karstic topography including a probable pinnacle structure. A synthetic modelling study was carried out, and it validated the reliability of the results. Finally, the findings indicated that the geophysical survey techniques used here were successful in detecting limestone deposits through the rather vertical terrain difficult to traverse carrying ground penetrating radar or resistivity instruments, which are usually employed to explore limestone deposits. The magnetic survey was also cost effective with respect to the cost demands of the other possible geophysical techniques. The study results were digitised from GEM-systems magnetic data loggers by Oasis Montaj and was exported to mapping software, MapInfo. To access the geodatabase the user needs to have ArcGIS 8.3 or later and basic EXCELL software.